Analisis Kematangan Emosi dalam Membentuk Kesiapan Belajar Siswa - Okta Zahratul Jannah; Ica Efilia Natasya; Dwi Purwanti; Desi Rismayanti; Ira Ristanti; Martini Martini; Liza Murniviyanti; Arizona Arizona (Scidacplus, 2026)
This study analyzed the relationship between emotional maturity and students' learning readiness at SDN 17 Kayuagung. Using a descriptive qualitative approach, data were collected through direct observation and documentation of student development records. The results showed that emotional maturity is a key determinant in shaping learning readiness. Students with good emotional regulation demonstrate high focus, strong motivation, and active participation in learning. Conversely, emotional instability is a significant barrier to student concentration and engagement in class. The study's conclusions confirm that improving learning readiness in elementary schools requires strengthening psychological factors and the learning environment, in addition to academic factors.